Seven lessons from the e-Peso pilot plan: The possibility of a Central Bank digital currency - Adolfo Sarmiento (Latin American Journal of Central Banking (LAJCB), 2022)
The decision to introduce a central bank digital currency (CBDC) is part of the new challenges that central banks are facing as technology keeps moving. The e-Peso pilot plan, implemented between 2017 and 2018, could provide some key findings for central banks. In this sense, we can learn seven lessons from the e-Peso pilot plan: (i) reputation is key for central banks' decision to introduce a CBDC; (ii) financial inclusion and cultural reasons are the main motivations; (iii) the technological solution as simple as possible; (iv) security aspects and traceable transfers are central for operational risk problems; (v) a token was a good solution for CBDC implementation; (vi) digital money was used for small payments and transfers; and (vii) CBDCs complement the existing means of payment. The conclusions highlight that CBDC choices are based not only on technical considerations but also on the cultural implications money use. The adoption of this new means of payment will be incremental but not reversible.
Keywords: E42; E58; G21; 330; Central banking; CBDC; Central bank digital currency; Digital currency; Digital money; Payment systems